Increasing extreme melt in northeast Greenland linked to foehn winds and atmospheric rivers - Kyle S. Mattingly; Jenny V. Turton; Jonathan D. Wille; Brice Noël; Xavier Fettweis; Åsa K. Rennermalm; Thomas L. Mote (Nature Communications, 2023)
Abstract The Greenland Ice Sheet has been losing mass at an increased rate in recent decades. In northeast Greenland, increasing surface melt has accompanied speed-ups in the outlet glaciers of the Northeast Greenland Ice Stream, which contain over one meter of sea level rise potential. Here we show that the most intense northeast Greenland melt events are driven by atmospheric rivers (ARs) affecting northwest Greenland that induce foehn winds in the northeast. Near low-elevation outlet glaciers, 80–100% of extreme (> 99th percentile) melt occurs during foehn conditions and 50–75% during ARs. These events have become more frequent during the twenty-first century, with 5–10% of total northeast Greenland melt in several recent summers occurring during the ~1% of times with strong AR and foehn conditions. We conclude that the combined AR-foehn influence on northeast Greenland extreme melt will likely continue to grow as regional atmospheric moisture content increases with climate warming.